Balance of Na+, K+, and Cl– Unidirectional Fluxes in Normal and Apoptotic U937 Cells Computed With All Main Types of Cotransporters - Yurinskaya, Valentina E.; Vereninov, Igor A.; Vereninov, Alexey A. (Frontiers in Cell and Developmental Biology, 2020)
Fluxes of monovalent ions through the multiple pathways of the plasma membrane are highly interdependent, and their assessment by direct measurement is difficult or even impossible. Computation of the entire flux balance helps to identify partial flows and study the functional expression of individual transporters. Our previous computation of unidirectional fluxes in real cells ignored the ubiquitous cotransporters NKCC and KCC. Here we present an analysis of the entire balance of unidirectional Na+, K+, Cl– fluxes through the plasma membrane in human lymphoid U937 cells taking into account not only the Na/K pump and electroconductive channels but all major types of cotransporters NC, NKCC, and KCC. Our calculations use flux equations based on the fundamental principles of macroscopic electroneutrality of the system, water balance, and the generally accepted thermodynamic dependence of ion fluxes on the driving force, and they do not depend on hypotheses about the molecular structure of the channel and transporters. A complete list of the major inward and outward Na+, K+, Cl– fluxes is obtained for human lymphoid U937 cells at rest and during changes in the ion and water balance for the first 4 h of staurosporine-induced apoptosis. It is shown how the problem of the inevitable multiplicity of solutions to the flux equations, which arises with an increase in the number of ion pathways, can be solved in real cases by analyzing the ratio of ouabain-sensitive and ouabain-resistant parts of K+ (Rb+) influx (OSOR) and using additional experimental data on the effects of specific inhibitors. It is found that dynamics of changes in the membrane channels and transporters underlying apoptotic changes in the content of ions and water in cells, calculated without taking into account the KCC and NKCC cotransporters, differs only in details from that calculated for cells with KCC and NKCC. The developed approach to assessment of unidirectional fluxes may be useful for understanding functional expression of ion channels and transporters in other cells under various conditions. Attached software allows to reproduce all calculated data under presented conditions and to study the effects of the condition variation.